Community, Village, Gender, and Social Inclusion: A Literature Review - Ariyanto, Komang (Talenta Publisher, 2024)
This article provides a summary of the literature review on the relationship between community, villages, gender, and social inclusion in community development. The researchers investigate how these factors interrelate and influence social inclusion. The article outlines the role of communities and villages in promoting social inclusion and how gender influences these dynamics. The study emphasizes the multifaceted nature of inclusivity in community development, including spatial, social, environmental, economic, and political dimensions. Attention is given to meaningful participation in decision-making processes and proposals for empowering marginalized groups. The research underscores the importance of social inclusion in sustainable urban development, particularly for addressing the needs of disadvantaged groups. It highlights the necessity for more inclusive community development policies and practices that prioritize meaningful participation, social inclusion, and equality.